2014
DOI: 10.1177/2050640613510905
|View full text |Cite
|
Sign up to set email alerts
|

Fructose‐induced symptoms beyond malabsorption in FGID

Abstract: The dietary carbohydrate fructose can be incompletely absorbed in the small intestine and is sometimes associated with gastrointestinal symptoms that include motility disturbances and abdominal pain. Fructose malabsorption has been well documented in variable but similar proportions of healthy and populations with functional gastrointestinal disorders. Recent work into the expression of the main intestinal fructose transporter proteins highlight that our understanding of the mechanistic basis for fructose mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…However, they remain inconclusive, as no glucose and fructose transporters (GLUT2) or EFF transporters (GLUT5) genetic mutations have been identified, nor is there evidence that depressed levels of these transporters are responsible for the condition (18)(19)(20)(21) . Rather, research suggests that our current food supply contains EFF (high fructose: glucose ratios), from HFCS, agave syrup, crystalline fructose, apple juice and other combination juices with apple juice, that we have not evolved to consume (19,20) . Notably, the list of foods that naturally contain high fructose:glucose ratios is short.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they remain inconclusive, as no glucose and fructose transporters (GLUT2) or EFF transporters (GLUT5) genetic mutations have been identified, nor is there evidence that depressed levels of these transporters are responsible for the condition (18)(19)(20)(21) . Rather, research suggests that our current food supply contains EFF (high fructose: glucose ratios), from HFCS, agave syrup, crystalline fructose, apple juice and other combination juices with apple juice, that we have not evolved to consume (19,20) . Notably, the list of foods that naturally contain high fructose:glucose ratios is short.…”
Section: Discussionmentioning
confidence: 99%
“…They found that fructose, as remains in the digestive tract of fructose malabsorbers, forms AGEunder conditions compatible with the intestineswithin a time frame well within the window of digestion, but not with glucose (16,17) . Notably, fructose malabsorption occurs after consumption of foods and beverages with high fructose:glucose ratios, (18)(19)(20)(21) including HFCS (22)(23)(24) , agave syrup (25,26) , crystalline fructose and apple juice (27) , but not after consumption of sucrose or equivalent monomers of fructose and glucose (18)(19)(20)(21) . Importantly, researchers from the University of California found that fructose to glucose ratios (1•9:1 (28) and 1•5:1 (29) ) in popular US sodas exceeded levels that are generally recognised as safe (1•2:1) (22)(23)(24) , which provided evidence that there has been more excess free fructose (EFF) in the US food supply than previously thought.…”
mentioning
confidence: 99%
“…[56] Notably, few natural foods contain significantly more fructose than glucose. Exceptions include apples, pears, watermelons, and mangoes [35].…”
Section: Discussionmentioning
confidence: 99%
“…This usually follows ingestion of food or beverages that contain a ratio of fructose to glucose greater than 1 [21,23]. Otherwise, enhanced absorption of fructose by glucose would tend to shorten contact times.For instance, fructose malabsorption due to large intake of high fructose corn syrup (HFCS) and apple juice has been shown [28][29][30][31] We show a time and dose dependent formation of fluorescent AGEs between fructose (but not glucose) and OVA during simulated digestion at concentrations plausibly found in the gastrointestinal lumen (10-50 mmol/l). Indeed, in the typical Western diet over 200 mmoles of fructose in liquid form can be ingested in two glasses of apple juice or soda usually together with a load of protein and fat that delays gastric motility [32][33].…”
Section: Discussionmentioning
confidence: 98%
“…It has been proposed that the association is due to RAGE activation by AGE adducts formed in situ in the intestines when fructose, peptides and amino acids co-exists for abnormally long periods [15,21,23,28,31]. We chose OVA not only as a well-studied classic model protein to be employed in simulated digestion employed but also as a key allergenic per se.…”
Section: Discussionmentioning
confidence: 99%